Relapsed Brucellosis Manifested as Endocarditis with Vegetation on the Implantable Cardioverter Defibrillator Lead - Bisher Sawaf; Wael Kanjo; Yasir Alabbas; Ahmad Hatim; Unus K. Bedardeen; Wafer A. Dabdoob (Case Reports in Cardiology)
Implantable cardioverter defibrillator lead endocarditis due to Brucella melitensis is a rare and life-threatening complication of brucellosis. Successful management requires a combination of medical treatment and device extraction. We present a case of relapsing brucellosis manifested as infective endocarditis colonizing the lead of the implantable cardioverter defibrillator with formation of vegetation on the lead. A 63-year-old male presented to the rehabilitation unit with hypotension. No other signs of infection were noted. The patient had a history of drinking unpasteurized milk since childhood and a previous episode of Brucella infective endocarditis. A transthoracic echocardiography showed an oscillating vegetation on the lead of the tip of the right atrial ICD, and the blood cultures were positive for Brucella melitensis. Surgical removal of the device was infeasible, and medical management was the only feasible option in this case.